Effects of Antibiotics, Salt and pH on the Hatchability of Fasciola Gigantica Eggs: Short Communication (2001)
A study was carried out to examine the effects of various antibiotics, salt concentrations and pH on the hatchability of F. gigantica eggs. It was observed that tetracycline concentration of 0.5mg/ml and above inhibited the development and hatching of F. gigantica eggs. Salt concentration of 1% gave low hatchability while 2% concentration and above strictly inhibited the hatching of the eggs. Acidic pH of 3-5 inhibited hatching of F. gigantica eggs while pH of 7-8 promoted hatching of eggs to above 3.4%. The possibility of employing the results of this study to fashion out a control measure against fasciolosis in farm animals is discussed.